2016
DOI: 10.1177/009164711604400401
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Psychology and Missions in JPT: Looking Back, Around, and Forward

Abstract: influential to psychology practitioners and researchers involved in missions. Member Care. O'Donnell (1997), in his seminal article, "Member care in missions: Global perspectives and future directions," provided the now frequently referenced definition of the term member care: "Member care is the ongoing investment of resources by mission agencies, churches, and other mission organizations for the nurture and development of missionary personnel. It focuses on everyone in missions (missionaries, support staff, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…On completion of identification, screening, and the assessment process, nine articles were included, which either gave commentary on how psychological assessments should be conducted or which reported personality assessments in candidates applying to work in church ministry or cross-cultural mission. A further five articles (Barnett et al, 2005;Cousineau et al, 2007;Isacco et al, 2020aIsacco et al, , 2020bRosik et al, 2016) were added based on the bibliography of these nine articles (Crawford & Wang, 2016;Dimos & Hasz, 2017;Ferrari, 2017;Gingrich, 2016;Jack & Wilcox, 2018;McGlone & Sperry, 2020;McGlone & Viglione, 2020;Rosik et al, 2017;Thomas & Plante, 2015). Jack and Wilcox (2018) published the only article that was not based on a US sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On completion of identification, screening, and the assessment process, nine articles were included, which either gave commentary on how psychological assessments should be conducted or which reported personality assessments in candidates applying to work in church ministry or cross-cultural mission. A further five articles (Barnett et al, 2005;Cousineau et al, 2007;Isacco et al, 2020aIsacco et al, , 2020bRosik et al, 2016) were added based on the bibliography of these nine articles (Crawford & Wang, 2016;Dimos & Hasz, 2017;Ferrari, 2017;Gingrich, 2016;Jack & Wilcox, 2018;McGlone & Sperry, 2020;McGlone & Viglione, 2020;Rosik et al, 2017;Thomas & Plante, 2015). Jack and Wilcox (2018) published the only article that was not based on a US sample.…”
Section: Resultsmentioning
confidence: 99%
“…Two opinion/review articles have been written on this topic since the year 2000, which indicated a clear need for more research in this area (Crawford & Wang, 2016; Gingrich, 2016). These papers highlighted that pre-service psychological assessment is a key part of reducing attrition in cross-cultural missions (Crawford & Wang, 2016). These psychological assessments also need to take into account the added complexity of assessing family systems, as it is often a whole family unit that is working cross-culturally, rather than just an individual (Gingrich, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations